BILATERAL CONTRACTED FLEXOR TENDON AND ITS SURGICAL MANAGEMENT IN A CALF - Das, Jaykrushna; Behra, Sidhartha Sankar; Senapati, Manas Ranjan; Behra, Monalisa; Behram, Ananta (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
Congenital flexural deformities usually involve the carpal or fetlock joints and ranges in severity from mild flexion of one joint to severe flexion of several joints and inability to walk, stand and suckle (Fubini and Ducharme, 2004). This condition is involving the flexor tendons of one or both fore limbs or hind limbs, but front limbs are primarily affected . Etiology includes inherited factors (autosomal recessive gene), in-utero malpositioning, large size of foetus, toxicity and mineral and vitamin deficiency during pregnancy (Kumar et al., 2012). The present report communicates successful surgical management of bilateral forelimb fetlock joint knuckling in a jersey calf.